Development of the Special School in Ukraine as the Expression of External Differentiation of Secondary Education: Methodological Accompaniment in 1944-1948 - Dichek, Natalia (Pedagogical Discourse, 2013)
In the context of individualization of educational process for the first time on the basis of the archived sources was discovered the contribution in 1944-1948 of the Scientific and Research defectology institute of the Ministry of education of USSR in to development of schools for children with the special necessities. Subjects and scientific products of workers (methodical recommendations, teaching programs, textbooks), their influence on deepening of the differential approach to diagnostics and education of children with defects of psychophysical development. Taking into account the political and ideological features of historical time the positive lines of establishment’s activity (study of work of the special schools and methodical help to their teachers) and shortcomings (absence of experimental and scientific researches) are considered. The usage of earlier unknown facts gave an opportunity to enter into scientific everyday life the refined data about functioning of Institute.